2013
DOI: 10.1155/2013/382635
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Influence of the Forming Strategy on the Main Strains, Thickness Reduction, and Forces in a Single Point Incremental Forming Process

Abstract: This paper comprises an experimental study for a complex geometry part obtained by incremental forming. Due to the process complexity (the presence of forces on three directions—a vertical one and two in the blank's plane), a three axes CNC milling machine, capable of describing the complex paths covered by the punch for obtaining the truncated cone-shaped parts, has been chosen. To obtain a truncated cone, three different trajectories were selected: in first and second variants after each vertical press havin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 18 publications
1
24
0
Order By: Relevance
“…Oleksik studied in paper [1] the thickness reduction of frustum cone shaped parts with different wall angles, ranging from 45° to 65°. The author also confirmed experimentally that the maximal values of the thickness reduction are accordingly with the sine law, but only after a certain height of the part is reached [6], [7], [8]. From experimental results it can be observed that for a steel sheet, regardless of the wall angle, step on vertical direction, diameter of the punch the thickness reduction was between 30% to 40% of the initial thickness of the sheet which is still not acceptable in many areas of industry and further represents a drawback of single point incremental forming process.…”
Section: Introductionmentioning
confidence: 63%
“…Oleksik studied in paper [1] the thickness reduction of frustum cone shaped parts with different wall angles, ranging from 45° to 65°. The author also confirmed experimentally that the maximal values of the thickness reduction are accordingly with the sine law, but only after a certain height of the part is reached [6], [7], [8]. From experimental results it can be observed that for a steel sheet, regardless of the wall angle, step on vertical direction, diameter of the punch the thickness reduction was between 30% to 40% of the initial thickness of the sheet which is still not acceptable in many areas of industry and further represents a drawback of single point incremental forming process.…”
Section: Introductionmentioning
confidence: 63%
“…The corner of the drawpiece is the most strained region in the sheet due to its complex stress state. The formability and morphology of crack initiation in the sheet (region of local sheet thinning) is a complex function of the tool path strategy [7,39,40], shape of the drawpiece [15,41], forming temperature [8,15], friction conditions [8,42], and vertical step down [15,38] used. The crack initiation was observed in the vicinity of the rib bottom and propagates along the edge of the truncated cone ( Figure 5).…”
Section: Formabilitymentioning
confidence: 99%
“…Analysis of surface topography in ISF has gained research interest in the past few years [7,8]. According to Lasunon et al [9] feed rate has little effect on the surface roughness, while the wall angle, depth increment, and its interaction play an important role.…”
Section: Introductionmentioning
confidence: 99%
“…MASTERCAM software has been used to create a tool path for feeding it to the three axis CNC vertical milling machine (DMC70V) for employing ISF. The spiral toolpath is considered as it is an optimized form of the tool path among other techniques [9,10]. The manufacturing parameters are considered as: Tool radius = 12 mm, step size = 0.25 mm, spindle speed = 250 rpm, feed rate = 1000 mm/min and lubrication = greese.…”
Section: Production Processmentioning
confidence: 99%